Embriologi Acardiac Twin - Hayati, Nur (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2010)
Acardiac twin is a rare congenital malformation ofmonochorionic twin, often result from extensive abnormalplacental anastomose. This leads to twin reversed-arterial-perfusion (TRAP) syndrome in the recipient twin, causing hypoxia to the cephalic pole leading to abnormalities of the upper body. This condition is always fatalfor the recipient twin and carries a high mortality for the pump twin. Purpose of this article is to review the embryology of acardiac twin. Case reported a 25 years old secundigravida was referred to Tirtonegoro Hospital, Klaten at 30 weeks of gestation with ultrasound report performed by an obstetrician as a single pregnancy with intraabdominal cystic mass. At 33 weeks of gestation the patient was labour a twin. The first was spontaneous, vertex presentation, female, 1600g without any external malformation and no sign for cardiomegaly. The second, by cesarean delivery, female, acardiac-anceps, stillborn, 1950g. Monoplacenta, diamnionic and monochorionic with second twinâ€™s umbilical cord 3 cm. This acardiac twin was not diagnosed in antenatal care. The conclusion is a rare case of acardiac twin has been reported and discussed embryologically. Acardiac twin is resulting from extensive abnormal placental vascular anastomosis between twins in monochorionic multiple pregnancies. Knowing the embryologic sequence is important to understanding the mechanism of twin placentation due to this unique syndrome.Acardiac twin adalah suatu bentuk malformasi kongenital langka pada kembar monochorion, akibat anastomosis ekstensif pada pembuluh darah plasenta, menyebabkan terjadinya twin reversed-arterial-perfusion (TRAP) syndrome pada kembar â€œresipienâ€ yang mengakibatkan hipoksia pada kutup kepala fetus dan selanjutnya terjadi abnormalitas pada badan bagian atas. Keadaan ini fatal bagi kembar resipien dan menyebabkan tingginya mortalitas dan morbiditas bagi kembar donor. Tujuan penulisan makalah ini adalah untuk menelaah embriologi kasus acardiac twin. Dilaporkan kasus seorang sekundigravida umur 25 tahun dirujuk ke RSU Tirtonegoro Klaten, pada umur kehamilan 30 minggu, hasil USG janin tunggal dengan masa kistik di abdomen. Pada umur kehamilan 33 minggu pasien melahirkan bayi kembar. Bayi I lahir spontan, presentasi kepala, perempuan, BB 1600 g, tidak ada malformasi eksternal dan tidak ada tanda cardiomegali. Bayi kedua lahir secara sectio sesaria, perempuan, acardiac- anceps, lahir mati, BB 1950 g. Plasenta monoplasenta, diamnion, monochorion dengan tali pusat janin II hanya 3 cm. Acardiac twin kasus ini tidak terdiagnosis pada saat ANC. Disimpulkan bahwa kasus yang jarang yaitu acardiac twin dan dibahas aspek embriologisnya. Acardiac twin terjadi karena adanya anastomosis abnormal pembuluh darah placenta pada kehamilan kembar monochorion. Memahami urutan embriologis penting untuk mengetahui mekanisme pembentukan plasenta yang berperan dalam kasus unik ini.